The Origin and Notion of Clothing and the Appearance of Inscriptions on the Items of Clothes - Sevara, Jumanova (European Journal of Life Safety and Stability (2660-9630), 2023)
The current article discusses the history and formation of the names of clothing. Besides the content is devoted to analyze the scripts and their meanings on the items of clothing.